Pre-treatment Process of Biodiesel Production From Waste Cooking Oil - Putri Restu Dewati; Achmad Halim Purbohandono; Arief Budiman (Eksergi)
Methyl ester of fatty acids known as biodiesel, synthesized from vegetable oils or animal fats, is a promising alternative fuel due to the limited resource of fossil fuel and the environment concern. There are large amount of low cost oil such as waste cooking oil that could be converted to biodiesel. However there is problem related to process of this low cost oil since they often contain large amounts of free fatty acid (FFA) that cannot be converted to biodiesel using alkalin ecatalyst. In this paper, a technique for reducing the FFA as pre-treatment in biodiesel production from waste cooking oil is studied. This pre-treatment step is aimed to esterify the FFA before trans-esterifying process of triglycerides with an alkaline-catalyst to complete the reaction. The main parameters of this process such as temperature, the molar ratio of methanol to acid catalyst, and catalyst loading were investigated to determine the optimum condition for converting of the FFA to usable esters. The result shows that the best condition for reducing of FFA was obtained at 65o C, with a molar ratio of oil to methanol of 1:6, and catalyst loading of 2 wt% H2SO4 .